MAPPING RESEARCH ON ABSTRACT ALGEBRA LEARNING; A BIBLIOMETRIC STUDY - Rindi Antika; Turmudi; Rizky Rosjanuardi; Endang Cahya Mulyaning Asih (Faculty of Educational sciences, UIN Syarif Hidayatullah Jakarta, 2026)
Abstract Abstract algebra plays a crucial role in undergraduate mathematics education by fostering axiomatic reasoning, structural thinking, and formal proof construction. Comprehensive mappings of the field remain limited. This study aims to identify global research trends in abstract algebra learning through a bibliometric analysis of 75 Scopus-indexed publications published between 1973 and 2025. Using Biblioshiny in R, the analysis examined publication growth, influential sources, authorship patterns, geographical distribution, citation impact, and thematic structures. The results indicate a substantial increase in research activity, particularly after 2010, with strong contributions from mathematics education journals and research communities in the United States and Europe. Thematic analysis reveals that group theory, instructional approaches, and mathematics education are the dominant topics, whereas issues related to epistemological transitions and learning obstacles remain underexplored. These findings provide an overview of the development of abstract algebra learning research and highlight opportunities for future design-based studies aimed at addressing learning obstacles in advanced mathematics education. Abstrak Aljabar abstrak merupakan mata kuliah penting dalam pendidikan matematika karena mengembangkan penalaran aksiomatis, pemikiran struktural, dan kemampuan pembuktian formal. Kajian yang memetakan perkembangan bidang ini secara komprehensif masih terbatas. Penelitian ini bertujuan menganalisis tren penelitian global tentang pembelajaran aljabar abstrak melalui studi bibliometrik terhadap 75 publikasi terindeks Scopus periode 1973–2025. Analisis dilakukan menggunakan Biblioshiny pada perangkat lunak R untuk mengkaji pertumbuhan publikasi, sumber yang berpengaruh, pola kepenulisan, distribusi geografis, dampak sitasi, dan struktur tematik penelitian. Hasil menunjukkan peningkatan publikasi yang signifikan, terutama setelah 2010, dengan kontribusi dominan dari jurnal pendidikan matematika serta peneliti di Amerika Serikat dan Eropa. Analisis tematik mengungkap dominasi topik teori grup, pendekatan pembelajaran, dan pendidikan matematika, sementara isu transisi epistemologis dan learning obstacles masih relatif kurang diteliti. Temuan ini memberikan gambaran perkembangan bidang serta mengidentifikasi peluang penelitian lanjutan untuk mengatasi hambatan belajar pada pembelajaran matematika tingkat lanjut.